Writing about misogyny in the Maghreb: Boudjedra and Monénembo confront gender-based violence - Adéchinan David ADÉKAMBI; Mamadi TRAORÉ; Zégbily MONÈMOU (International Journal of Scientific Research and Innovative Studies, 2025)
This study examines representations of misogyny and gender-based violence in the Maghreb through a comparative analysis of two novels: La Répudiation (1969) by Rachid Boudjedra and Bled (2016) by Tierno Monénembo. Using Claude Duchet's sociocritical approach, this research aims to identify the forms of expression of such violence, their underlying factors, and their inscription within a specific spatio-temporal framework. The analysis reveals that these forms of violence primarily stem from the patriarchal nature of Maghreb society and manifest through four main modalities: verbal, physical and sexual, psychological, and economic violence. The study also demonstrates how the narrative techniques employed by both authors contribute to the denunciation of these social phenomena. Keywords: misogyny, gender-based violence, Maghreb literature, sociocriticism, patriarchy Received Date: October 20, 2024 Accepted Date: November 11, 2025 Published Date: December 01, 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/525